2021
DOI: 10.15826/chimtech.2021.8.4.11
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of highly stable luminescent molecular crystals based on (E)-2-((3-(ethoxycarbonyl)-5-methyl-4-phenylthiophen-2-yl)amino)-4-oxo-4-(p-tolyl)but-2-enoic acid

Abstract: The synthesis of (E)-2-((3-(ethoxycarbonyl)-5-methyl-4-phenylthiophen-2-yl)amino)-4-oxo-4-(p-tolyl)but-2-enoic acid was performed. This organic compound was used as a building block for the organic molecular crystals with highly stable photoluminescence at ambient conditions, which has been established during 10 years of exploitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Furthermore, this method was applied to the synthesis of 3-(imino(thien-2-yl))furan-2(3H)ones derivatives, which include the pharmacophore fragment, Gewald aminothiophene [30] (Scheme 1). It was found that 2-(2-(4-R-benzoyl)hydrazono)-4-oxobutanoic and 2-(thiophen-2-ylamino)-4-oxobut-2-enoic acids and their derivativities exhibit analgesic [31,32], anti-inflammatory [16] antimicrobial activity [24] and photoluminescent properties [33,34]. We continue to search for new biologically active compounds with low toxicity [35] and expand the methods for the synthesis of 2,4-dioxobutanoic acid and 3-hydrazonofuran-2(3H)-one derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this method was applied to the synthesis of 3-(imino(thien-2-yl))furan-2(3H)ones derivatives, which include the pharmacophore fragment, Gewald aminothiophene [30] (Scheme 1). It was found that 2-(2-(4-R-benzoyl)hydrazono)-4-oxobutanoic and 2-(thiophen-2-ylamino)-4-oxobut-2-enoic acids and their derivativities exhibit analgesic [31,32], anti-inflammatory [16] antimicrobial activity [24] and photoluminescent properties [33,34]. We continue to search for new biologically active compounds with low toxicity [35] and expand the methods for the synthesis of 2,4-dioxobutanoic acid and 3-hydrazonofuran-2(3H)-one derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, various materials have been intensively studied in materials science, such as inorganic nanoparticles [1][2][3], molecular crystals [4][5][6], COF (covalent organic framework) [7,8]. Applications for these materials include electronics [9], cancer treatment [10], catalysis [11], etc.…”
Section: Introductionmentioning
confidence: 99%